Utilization of Social Media for Effectiveness of Learning Communication during the Covid-19 Pandemic - Utami R. A. Padang; Fithrah Dwi Ananda; Nurbaiti Nurbaiti (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The A social media is able to lead to the development of extraordinary communication and information technology. With the various features used by social media, it is able to change the comnaction style of today’s society. The presence of social media even has an impact on the way we communicate in all fields, such as marketing communications, political communication and communication in learning system. The purpose of this study is o explain how a teacher uses a social media effectively as a learning tool during the covid-19 pandemic. This reserch method is descriptive research. The result showed that teachers as informations facilitator were able to build effective online communication. Effective communication is communication that is always estabalished between teachers and students so that the goals or intrntions can be fulfilled as well as possible depending on how the communication or teachers convey the message.